Peran Model Pengembangan Pariwisata Berbasis Masyarakat (Community Based Tourism) Dalam Mewujudkan Pariwisata Berkelanjutan (Sustainable Tourism) di Bali - Indah Permatasari (Fakultas Hukum, Universitas Warmadewa, 2022)
Tourism industry is a collection of interrelated tourism businesses, which aim to meet the needs of tourists in the administration of tourism. Of course, in an effort to meet the needs of tourists for the purpose of organizing tourism, cooperation from various parties is needed, both the local community, government, local government, and tourism entrepreneurs. The local community plays a particularly important role in the development of the tourism industry. In fact, in the provisions of Article 5 of Law Number 10 of 2009 concerning Tourism, principles of tourism implementation are regulated, one of which is empowering local communities. The problem that then arises is that sometimes the development of the tourism industry is not directed at the development of sustainable tourism. This is indicated by the existence of several tourism supporting facilities that are built not in accordance with their designation. This research is an empirical legal research that uses primary and secondary data with the aim of revealing the role of community-based tourism development models in realizing sustainable tourism in Bali. The results of the research show that the community-based tourism development model puts emphasis on the active role or participation of the community in the development of tourism. Furthermore, one of the goals of the community-based tourism is to realize sustainable tourism development. The local community plays a very important role in realizing sustainable tourism. Roles of the government, local governments, and tourism entrepreneurs are also of great importance in the context of realizing sustainable tourism.